Coinage and Neologism in Hausa Political Programs: A Sociolinguistics Perspective - Zailini, Abdulkadir Abu Bakar (Register Journal, 2019)
Linguistic aspect of language development is not an event that occur abruptly; rather, it pass through processes that take place gradually over time, in a stage by stage development. This paper dwells on linguistic issues on coinage and neologism arising in Hausa political programmes in the media, from the sociolinguistic perspective, which gave birth and rebirth of words/phrases meaning. New words/phrase are created, the existing ones are lexically and semantically expanded to accommodate new meanings in Hausa language usage. It observes and explains how some Hausa lexical items as well as sentences are used in the media political programmes in such a way that the language has new words and meanings; and instances of coinage and neologism in Hausa in the media are discussed.